Daunorubicin and Platelet Function - Pogliani, M E; Fantasia, R; Lambertenghi-Deliliers, G; Cofrancesco, E (Thrombosis and Haemostasis, 1981)
The influence of Daunorubicin on some platelet functions in vitro was investigated, using different concentrations of the drug (0.01-0.02-0.04 μg/ml). Daunorubicin was shown to inhibit Collagen and Thrombin induced platelet aggregation and the intensity of inhibition depended on both drug concentration and the time of preincubation.Daunorubicin was also shown to inhibit the release reaction, the platelet prostaglandin pathway and the availability platelet factor 3; the drug at concentrations for clinical use does not damage the platelet membrane, as is the case with the freezing and thawing test, in platelet uptake of 14C-serotonin and as confirmed by the electron microscope. When very high doses (0.16 mg) of Daunorubicin are used, lysis of the platelets can be observed and this is confirmed under the electron microscope by the presence of empty platelets with fractures at the level of the cytoplasmic membrane.Finally, Daunorubicin causes irreversible inhibition of reptilase clot-retraction, even if this is less severe than with Vincristine. Working with gel-filtered platelets, it would appear that the inhibition exercised by the drug on platelet reactions is not caused through modifications in Ca++ metabolism.The authors suggest that Daunorubicin, at the dosages used clinically, induces in vitro thrombocytopathy without damaging the cellular membrane as confirmed by the electron microscope.This impairment of platelet functions could play a part in hemorrhagic diathesis observed during Daunorubicin therapy.
Keywords: Inhibitors; Thrombocytopathy; Electron microscope morphology; Ca+ + metabolism; Release reaction